O item linguístico mesmo: confrontando usos e funções no português do Brasil - Amorim, Neide Correia Sant anna de (2009)
This study focuses on the linguistic item mesmo and its behavior in Brazilian Portuguese in different synchronic moments, therefore a panchronic approach. It adopts two empirical sources: i) sociolinguistic interviews from Corpus Variação Linguística da Paraíba (Oliveira, 2004); ii) official letters from 18th and 19th centuries, from Paraíba, extracted from Corpus Lingüístico Diacrônico da Paraíba (Fonseca, 2005). The study aims at understanding and explaining the different usages of the item mesmo in Modern Portuguese. The assumption here is that the multifunctionality of the item observed in today s speech is motivated by cognitive and pragmatic pressure. The theoretical background adopted are the postulates of Functional Linguistics, especially those proposed by Heine (1991), Traugott & Heine (1991), Hopper (1987; 1993) Hopper & Traugott (1993), Givón (1979; 1995), Votre (1996), Neves (1997; 2001), Martelotta (1996; 2003). As for the methodological aspects, both quantitative and qualitative perspectives were taken into account in the following order: first, synchronic data, and then, diachronic data. The results were, then, compared, trying to attest regularities and innovations of the item in the selected synchronic moments. In Modern Portuguese, the functional aspects of the item have been extended (grammaticalized), highlighting its referential value. This study also aims to contribute to the didactic treatment of the item mesmo, offering suggestions of activities in the classroom.